A proposed norms' benefits awareness framework for norms adoption - Itaiwi A.-M.K.; Ahmad M.S.; Tang A.Y.C.; Mahmoud M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Multi agent systems; benefits awareness; Mining algorithms; Normative system; norms; Norms detections; Software agents